The relationship technology acceptance and employee job performance in Pejabat Pendidikan Daerah Samarahan, Sarawak / Faiqah Japar - Japar, Faiqah (2016)
Technology acceptance has huge impact towards employee job performance. The variables included in technology acceptance model are perceived usefulness, perceived ease of use and behavioral intention to use. The objectives fur this study are to identify the relationship between technology perceived usefulness, perceived ease of use, technology behavioral intention to use and job performance am.mg the employees at Pejabat Pendidikan Daerah Samarahan, Sarawak. This study has fucuses on 186 staff in Organizational Management unit at Pejabat Pendidikan Daerah Samarahan, Sarawak. The result shared that technology acceptance model has strong relationship towards employee job performance at Pejabat Pendidikan Daerah Samarahan, Sarawak. Hence, some recommendations and suggestion for organization, employees and future researcher have been highlighted fur future study.